Network Pharmacology and bioinformatics analyses identify intersection genes of niacin and COVID-19 as potential therapeutic targets - Li, Rong; Li, Yu; Liang, Xiao; Yang, Lu; Su, Min; Lai, Keng Po (Briefings in bioinformatics, 2021)
Abstract Objectives Patients with colorectal cancer (CRC) may be susceptible to the coronavirus disease-2019 (COVID-19). However, anti-CRC/COVID-19 treatment options are currently unavailable. Since niacin is a vitamin with cytoprotective and anti-inflammatory functions, this study aimed to evaluate the possible functional roles and underlying mechanisms of action of niacin as an anti-COVID-19 and -CRC therapy. Interventions We used a series of network pharmacology-based and computational analyses to understand and characterize the binding capacity, biological functions, pharmacological targets and therapeutic mechanisms of niacin in CRC/COVID-19. Measurements and main results We revealed the clinical characteristics of CRC patients and COVID-19 patients, including predisposing genes, survival rate and prognosis. Moreover, the results of molecular docking analysis indicated that niacin exerted effective binding capacity in COVID-19. Further, we disclosed the targets, biological functions and signaling pathways of niacin in CRC/COVID-19. The analysis indicated that niacin could help in treating CRC/COVID-19 through cytoprotection, enhancement of immunologic functions, inhibition of inflammatory reactions and regulation of cellular microenvironment. Furthermore, five core pharmacological targets of niacin in CRC/COVID-19 were also identified, including BCL2L1, PTGS2, IL1B, IFNG and SERPINE1. Conclusions This study, for the first time, revealed the niacin-associated molecular functions and pharmacological targets for treating CRC/COVID-19, as COVID-19 remains a serious pandemic. But the findings were not validated in actual CRC patients infected with COVID-19, so further investigation is needed to confirm the potential use of niacin for treating CRC/COVID-19.